Chronic stable asthma and the normal arterial pressure of carbon dioxide in hypoxia. Issue 6242 (13th September 1980) - Cochrane, G M; Prior, J G; Wolff, C B
Abstract : Arterial blood-gas tensions, pH, and peak expiratory flow rate were measured in 29 patients with chronic asthma in a stable state. The hypoxia in these patients was found to be comparable with the hypoxia seen in normal subjects at high altitude in its effects on arterial pressure of carbon dioxide (PaCO2). These results suggest that in patients with asthma the PaCO2 taken as normal should be related to the arterial oxygen tension. Any increase in the observed value compared with this predicted value indicates impaired respiratory control. This may well help in assessing the patients at greatest risk during an attack of asthma.